KECERDASAN EMOSI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN DI KANTOR UNIVERSITAS PATTIMURA AMBON - Jennifer Christine Brand; Sutarto Wijono (Jurnal Cakrawala Ilmiah, 2023)
The purpose of this study was to determine the relationship between Emotional Intelligence and Organizational Citizenship Behavior among employees at Pattimura University, Ambon. The participants in this study were 41 employees at the Ambon Pattimura University Office through engineering Saturation Sampling. The data collection method uses the Google Form, where there are 28 items of Emotional Intelligence and 30 items of OCB. The Emotional Intelligence variable is measured using the five dimensions of Goleman (2000), namely; know one's emotions, manage emotions, self-motivation, empathy and build relationships. Meanwhile, the OCB variable is measured using the five dimensions of Organ (1988), namely;altruism, civic virtue, sportsmanship, dan conscientiousness. From the results of this study it was stated that there was a significant positive relationship between Emotional Intelligence and Organizational Citizenship Behavior. In other words, the higher the emotional intelligence, the higher the employee's OCB. Conversely, the lower the Emotional Intelligence, the lower the employee's OCB.